Sistem Tracking Objek Menggunakan Metode Edge Detection pada Quadcopter - Dimas Bagus Jatmiko; Gembong Edhi Setyawan; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Tracking objects are usually used to determine the position of objects and environmental conditions around the object. Objects that require supervision to be able to run properly require a system to monitor the object. Quadcopter is a type of UAV (Unmanned Aerial Vehicle) that can do several movements (pitch, yaw, roll and gaz). With a camera on a quadcopter, every movement of the object will be known directly through the camera image. So that in this study a system was created to detect and track objects. Applying an image processing system based on image processing using the shape detection method. Then displays the detection results in the frame image which is divided into 9 grids and tracks the object in the form of forward, backward, upward, downward, turn right and turn left. System will be tested based on tracking accuracy of objects. From the testing of object tracking accuracy obtained an average success of 76,6%, failure of 23,4% caused by uncertain lighting in the room and objects with shapes resembling objects that are tracking.